2021
DOI: 10.31557/apjcp.2021.22.11.3483
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and Radiological Features with Long Term Follow Up of Metaplastic Carcinoma Breast in India

Abstract: Objective: Metaplastic breast carcinoma (MBC) is a heterogeneous group of invasive carcinomas with squamous and/or mesenchymal differentiation. Because of their rare occurrence, the information regarding the clinical behaviour of metaplastic carcinomas is limited. The purpose of our study was to delineate the clinicopathological and radiological features, treatment outcomes, prognostic factors, and survival of patients with MBC. Methods: Ambispective observational study with prospective recruitment was done fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Jia et al [13] reported MBC in association with calcifications on mammography in only 3 of 13 cases and described calcifications as pleomorphic, coarse heterogeneous, and fine linear branching. In another case series, calcifications were present on mammography in 3 of 22 cases and described as pleomorphic [14] . Coarse calcifications were reported in a case of MBC with osseous differentiation, [17] .…”
Section: Clinical and Imaging Presentationmentioning
confidence: 95%
See 1 more Smart Citation
“…Jia et al [13] reported MBC in association with calcifications on mammography in only 3 of 13 cases and described calcifications as pleomorphic, coarse heterogeneous, and fine linear branching. In another case series, calcifications were present on mammography in 3 of 22 cases and described as pleomorphic [14] . Coarse calcifications were reported in a case of MBC with osseous differentiation, [17] .…”
Section: Clinical and Imaging Presentationmentioning
confidence: 95%
“…The maximum dimension of the mass was 7.2 cm by surgical pathology. Other reports of MBC describe mass measurements at initial presentation as greater than 2 cm [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] . Many cases of MBC also present clinically as a rapidly growing mass [16 , 19] .…”
Section: Clinical and Imaging Presentationmentioning
confidence: 99%